Efficiency of four trap types and human landing catch in the sampling of Mansonia (Diptera, Culicidae) in Porto Velho, Rondônia, Brazil. - Nercy Virginia Rabelo Furtado; José Ferreira Saraiva; Kaio Nabas Ribeiro; Noel Santos Fernandes Neto; Jéssica Fernanda Dos Santos Barroso; Cynara de Melo Rodovalho; Dario Pires Carvalho; Allan Kardec Ribeiro Galardo; José Bento Pereira Lima (PLoS ONE)
Entomological surveillance plays a crucial role in designing and implementing mosquito control measures. In this context, developing more effective collection strategies is essential to accurately estimate the entomological parameters necessary for effective control. In this study, we investigated the effectiveness of four traps: CDC light trap, MosqTent, BG-Sentinel, and SkeeterVac, compared to human landing catch (HLC) in the collection of Mansonia mosquitoes, known to cause discomfort to riverside populations along the Madeira River in the District of Jaci Paraná, Porto Velho, in Rondônia state, Brazil. Sampling was conducted, during three periods corresponding to two seasons, dry and rainy, over five consecutive days for each period. The captures using HLC and the installation of the traps took place on the grounds of five selected residences from 6 to 10 pm. Rotational exchanges between houses ensured that all traps and the HLC were used in each of the five residences, following a predetermined Latin square pattern. A total of 7,080 mosquitoes were collected, of which 90.5% belonged to the Mansonia genus, distributed in four species: Mansonia titillans (75.97%), Mansonia humeralis (18.91%), Mansonia amazonensis (1.90%), and Mansonia indubitans (1.37%). HLC captured the highest number of Mansonia mosquitoes (58.1%), followed by SkeeterVac (21.8%) and MosqTent (18.9%). CDC and BG-Sentinel showed a very low performance (0.92 and 0.23%, respectively). Although HLC performed better in capturing Mansonia, our results suggest that SkeeterVac and MosqTent can serve as valuable additional tools to entomological inventories or sentinels for detecting invasive species in areas with high epidemiological vulnerability, thereby providing evidence-based recommendations for improving mosquito control measures and entomological surveillance.